Construction and characterization of a full-length complementary DNA infectious clone of emerging porcine Senecavirus A - Yuan, Fangfeng (Kansas State University, 2017)
Seneca Valley Virus (SVV) causes vesicular disease in pigs. Vesicular lesions on the snout and coronary band of hoof mostly resemble lesions caused by Foot-and-Mouth Disease Virus (FMDV), which may lead to the foreign animal disease investigation. In 2015, Brazil experienced major outbreaks of SVV; then in July, sporadic cases of SVV were reported in United States and became a concern in swine industry. A reverse-genetic system serves as a major tool to study pathogenesis of the virus. In our study, a full-length cDNA infectious clone, pKS15-01-Clone, was constructed from an emerging Seneca Valley Virus (SVV; strain KS15-01). To explore the potential use as a viral backbone for expressing marker genes, the enhanced green fluorescent protein (EGFP)-tagged reporter virus (vKS15-01-EGFP) was generated using reverse genetics. Compared to the parental virus, the pKS15-01-Clone derived virus (vKS15-01-Clone) replicated efficiently in vitro and in vivo, and induced similar levels of neutralizing antibody and cytokine responses in infected animals. In contrast, the vKS15-01-EGFP virus showed impaired growth ability and induced lower level of immune response in infected animals. Lesions on the dorsal snout and coronary bands were observed in all pigs infected by parental virus KS15-01, but not in pigs infected with vKS15-01-Clone or vKS15-01-EGFP viruses. These results demonstrated that the infectious clone and EGFP reporter virus will be important tools in further elucidating the SVV pathogenesis and development of control measures.
Keywords: Senecavirus A; Infectious clone; EGFP reporter virusVirology